2014
DOI: 10.1111/jace.13103
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self‐Activated Zinc Gallogermanate Phosphor: The Origin of its Photoluminescence

Abstract: Since 2012, zinc gallogermanate has drawn interests as an excellent host phosphor for a variety of dopants (e.g., Cr3+, Bi3+ and Mn2+). However, the origin of its self‐activated luminescence has been largely unknown. Here, zinc gallogermanate of the composition Zn1+xGa2−2xGexO4 (0 ≤ x ≤ 1) is prepared by solid‐state reaction, and the evolution of the crystal structure with the composition is studied. The phosphors show a broad white‐bluish emission upon excitation by ultraviolet (UV) light, and the luminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 27 publications
5
43
0
Order By: Relevance
“…The compositional evolution of the XRD patterns accord with Allix's work on the same materials as those studied in this work [9]. A more detailed study on the structure of zinc gallogermanate phosphors can also be referred to our recent publication [11].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The compositional evolution of the XRD patterns accord with Allix's work on the same materials as those studied in this work [9]. A more detailed study on the structure of zinc gallogermanate phosphors can also be referred to our recent publication [11].…”
Section: Resultssupporting
confidence: 85%
“…It is found that Ga 2 O 3 and GeO 2 get evaporated slightly during the preparation course. Previous EPR study of the non-doped zinc gallogermanate indicates that the host matrix contains the gallium and germanium vacancies, which act as the emitting centers responsible for the self-luminescence of the nondoped phosphors [10,11]. XRD patterns of the samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21 , it is very difficult to determine unambiguously the exact Zn 1+ x Ga 2−2 x Ge x O 4 phase in GCs, owing to the undistinguishable XRD patterns between the two end-members, ZnGa 2 O 4 ( x  = 0) and Zn 2 GeO 4 ( x  = 1). By comparing the Raman spectra of the crystallized glasses with the standard Zn 1+ x Ga 2−2 x Ge x O 4 polycrystals synthesized in our lab by solid-state reaction (for more detail, refer to our previous work 19 ), we provide the first direct evidence for the formation of Zn 1+ x Ga 2−2 x Ge x O 4 with x ≥ 0.4 in GCs (Fig. S1(b), supporting information).
Figure 1( a ) XRD patterns of the as-made Ni 2+ doped glass (ZGO-0.15PG), crystallized glass (ZGO-0.15GC) and standard ZnGa 2 O 4 crystal (PDF card no.
…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in this work, a simple fluorescence probe method was chosen, to prove the existence of VnormalO with its effect on LPL performance. At present, germanates have been developed as LPL phosphors due to their low synthesis temperature, high stability, and reasonable conductivity as an oxide host . In this work, Ca 2 Ga 2 GeO 7 (CGG) with self‐activated properties was chosen as the host matrix.…”
Section: Introductionmentioning
confidence: 99%